Role of Postoperative Vitamin D and/or Calcium Routine Supplementation in Preventing Hypocalcemia After Thyroidectomy: A Systematic Review and Meta-Analysis - Alhefdhi, Amal (AlphaMed Press, 2013)
BACKGROUND. Transient hypocalcemia is a frequent complication after total thyroidectomy. Routine postoperative administration of vitamin D and calcium can reduce the incidence of symptomatic postoperative hypocalcemia. We performed a systematic review to assess the effectiveness of this intervention. The primary aim was to evaluate the efficacy of routine postoperative oral calcium and vitamin D supplementation in preventing symptomatic post-thyroidectomy hypocalcemia. The second aim was to draw clear guidelines regarding prophylactic calcium and/or vitamin D therapy for patients after thyroidectomy. METHODS. We identified randomized controlled trials comparing the administration of vitamin D or its metabolites to calcium or no treatment in adult patients after thyroidectomy. The search was performed in PubMed, Cochrane Library, Cumulative Index to Nursing and Allied Health Literature, Google Scholar, and Web of Knowledge databases. Patients with a history of previous neck surgery, calcium supplementation, or renal impairment were excluded. RESULTS. Nine studies with 2,285 patients were included: 22 in the vitamin D group, 580 in the calcium group, 792 in the vitamin D and calcium group, and 891 in the no intervention group, with symptomatic hypocalcemia incidences of 4.6%, 14%, 14%, and 20.5%, respectively. Subcomparisons demonstrated that the incidences of postoperative hypocalcemia were 10.1% versus 18.8% for calcium versus no intervention and 6.8% versus 25.9% for vitamin D and calcium versus no intervention. The studies showed a significant range of variability in patients' characteristics. CONCLUSIONS. A significant decrease in postoperative hypocalcemia was identified in patients who received routine supplementation of oral calcium or vitamin D. The incidence decreased even more with the combined administration of both supplements. Based on this analysis, we recommend oral calcium for all patients following thyroidectomy, with the addition of vitamin D for high-risk individuals.